2001
DOI: 10.1046/j.1365-2591.2001.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction detection of Treponema denticola in endodontic infections within root canals

Abstract: Aim A 16S rDNA‐based polymerase chain reaction (PCR) method was used to detect the occurrence of Treponema denticola in root canals. Methodology Samples were collected from 54 single‐rooted teeth having carious lesions and necrotic pulps. DNA extracted from the samples was amplified using the PCR assay, which yielded a specific fragment of T. denticola 16S rDNA. Results T. denticola was detected in 10 of 29 asymptomatic cases (34.5%), eight of 15 root canals that were tender to percussion (53.3%), and five of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 27 publications
4
27
2
7
Order By: Relevance
“…We detected this species in 40% of the samples, but in low levels. Similarly to our data, Siqueira et al (24) and Baumgartner et al (25) also reported a high prevalence of spirochetes in samples from endodontic infections using a different molecular method. Thus, it seems that these difficult-to-grow microorganisms have been underestimated in the past, as well as their role in the etiology of endodontic infections.…”
Section: Discussionsupporting
confidence: 91%
“…We detected this species in 40% of the samples, but in low levels. Similarly to our data, Siqueira et al (24) and Baumgartner et al (25) also reported a high prevalence of spirochetes in samples from endodontic infections using a different molecular method. Thus, it seems that these difficult-to-grow microorganisms have been underestimated in the past, as well as their role in the etiology of endodontic infections.…”
Section: Discussionsupporting
confidence: 91%
“…Many of the species that are reported as new are split off from previously established genera and species, but the ease of identifying culturedifficult species and the specificity of PCR-based methods has meant that some additional species can be included as typical of the microbial flora of the infected root canal. These include spirochaetes, [31][32][33][34][35] and the species Tanerella forsythensis (formerly Bacteroides forsythus), [36][37][38][39][40] which are prevalent in infected root canals yet difficult to cultivate.…”
Section: Contribution Of Molecular Techniquesmentioning
confidence: 99%
“…이 같은 배양법을 보완, 보충하기위해 1990년대 이후 다양한 분자 유전학적기술, 즉 checkerboard DNA:DNA hybridization 25) , real time-PCR 26) , 16S rRNA(DNA)gene-directed PCR 27,28) 등을 34,44) . 브라질에서 감염근관을 대상으로 16S rRNA genedirected PCR방법으로 조사한 결과 T. denticola는 임상 증상과 연관성있게 나타나는 것은 아니지만 임상증상 유무 에 관계없이 살펴봤을 때 42�52%의 높은 이환율을 보였 다 [33][34][35] . 그러나 국내에서 감염근관을 조사한 Jung 등 30) .…”
unclassified
“…Distribution of bacteria in fistula*; Samples were obtained through the opening of the fistula, whereas the others from the infected the root canals. [33][34][35][36]37) . Table 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation